Halogen dryer for roselle tea production - Amiril Sahab, Abdul Sani; Muhammad Nur Qayyum, Kamarulbahrin (2021)
Dried Roselle is produced from heating by using Halogen lamp which emits radiation that generates heat and vaporizes the moisture (water) content of Roselle